IgE-expressing long-lived plasma cells in persistent sensitization - Xiong, Shiqiu; Jia, Yang; Liu, Chuanhe (Frontiers in Pediatrics, 2022)
Persistent allergies affect the quality of life of patients and increase economic burdens. Many clinical observations indicate the presence of IgE+ long-lived plasma cells (LLPCs), which account for the persistent secretion of specific IgE; however, the characteristics of the IgE+ LLPCs have yet to be identified clearly. In this review, we summarized the generation of IgE+ PCs, discussed the prosurvival factors in the microenvironment, and reviewed the unique IgE-BCR signaling, which may bring insights into understanding the survival mechanisms of IgE+ LLPCs.